Antioxidant properties of selected varieties of lettuce (Lactuca sativa L.) commercially available in Malaysia - Gan, Yao Zu; Azlan, Azrina (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
This study aimed to determine total antioxidant and antioxidant activity of selected local varieties of lettuce (Lactuca sativa L.). Five varieties (iceberg, butterhead, romaine, green coral and red coral) were subjected to DPPH radical scavenging activity and ferric reducing antioxidant power assay (FRAP) assays for determination of antioxidant activity. Total phenolic content and total flavonoid content were determined as total antioxidant. The EC50 values obtained from the DPPH radical scavenging assay ranged from 303.56 to 4485.41 μg/ml. The red coral lettuce had the lowest EC50 value indicating it possesses the highest antioxidant activity among the varieties. This variety also showed the highest FRAP value compared with the other varieties, where the values ranged from 48.05 to 2135.82 mM Fe2+/100 g fresh weight. Total phenolic content of samples ranged from 4.85 to 76.05 mg gallic acid equivalent/100 g fresh weight, with the red coral lettuce had the highest value. Total flavonoid content of the lettuce samples ranged from 2.28 to 21.96 mg quercetin equivalent/100 g fresh weight, and were significantly different (p < 0.05) among the samples. The EC50 values of DPPH radical scavenging activity and FRAP values among samples were highly correlated with total phenolic content and total flavonoid content. Among the different varieties of lettuce, red coral lettuce showed the highest total antioxidants and antioxidant activity. Therefore, consumers are encouraged to consume this lettuce more on a regular basis for gaining a better health.